Two methods of cord care in high-risk newborns: Their effects on hydration, temperature, pH, and floras of the cord area. (March 2015) - Ahn, Youngmee; Sohn, Min; Jun, Yonghoon; Lee, Eunyoung; Lee, Sangmi
This randomized clinical study explored the effects of two cord care methods on hydration, temperature, pH, and floras at the cord area in high-risk newborns. One group used the water method; and the other group used the alcohol method. Seventy-two newborns, including premature newborns, in the neonatal intensive care unit (NICU) of a university-affiliated hospital in South Korea were enrolled from August 2011 to May 2012. Hydration, temperature, pH, and floras were measured daily until the cords fell off. The results showed no difference between the groups in hydration, temperature, pH, and the colonization of floras, but cord detachment in the alcohol group took 2 days longer (12.8 [5.7] days) than in the water group (10.9 [4.1] days). Our findings suggest that the clean-and-dry method of cord care, which uses water, could be sufficient, possibly even better than alcohol in maintaining the physiologic surface milieu of the cord area with less chance of infection and manipulation in NICUs with optimal infection control.